EXPERIMENTAL STUDY OF LOGS FROM SHILIKTY CEMETRY (East Kazakhstan) (Journal of history-rus, 2022)
The article presents data from an experimental study of the technological function of the cross-cutting eyelets in the logs found in the wooden-stone part of the mound № 1 of the Shilikty-3 burial ground which located in East Kazakhstan. According to the earlier dendrochronological analyzes of wood materials, the age of the mound № 1 is determined within the 7th century BC. The wooden part of the tomb was built of thick, butt-stacked larch logs in two rows, according to the cage-frame principle. Due to the fact that the forest required for the construction of the tomb was at a distance of 25 km from the burial site, the eyelets in larch logs were most likely used for dragging with horses. To verify this observation, the authors of the article conducted a full-scale experiment for the first time using materials available to the ancient society of the Saka culture. The study also established the time spent on operations. Three horses of the local breed were involved in the process of transporting the logs. During the experiment, it turned out that not every horse can cope with this kind of load. Thus, the results of the study showed the reliability of the above mentioned observation. So after dragging, traces of beveling become noticeable on the thin end of the log, similar to an archaeological source. In general, the experimental study of the technology used to cut and transport logs helps researchers to draw attention to those details of the daily life of ancient societies that previously seemed natural and did not require proof.